EFFECT OF NUTRITIONAL COUNSELING LEALEF MEDIA ON KNOWLEDGE, SODIUM, POTASIUM INTAKE IN PATIENTS HYPERTENSION - Dina Dwi Aprilia; Jumiyati Jumiyati; Ayu Pravita Sari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2021)
ABSTRACK Hypertension actually is a disease that can be implified on sudden death. It's mostly caused by high blood pressure so that the risk of suffering complications is a big issue. It can be caused by many factors, one of that is high sodium and low potassium consumption as well. Based on 2015 WHO data, it shows that 1.13 billion people in the world have hypertension. Based on Riskesdas data the number of cases of hypertension in Indonesia is 63,309,620 people. In Bengkulu province In 2018 about province's health data, it was found that in 2018 the estimated number of sufferers ≥ 15 years reached 899,010 people. The highest hypertension was found in the Selebar Sub-District Puskesmas Basuki Rahmad about 7,464 .The purpose of this study determines the effect of nutritional counseling using modified leaflet media, knowledge of sodium and potassium intake in patients with hypertension in Basuki Rahmad Community Health Center in Bengkulu City in 2020.This research method is a pre-experimental research design with one group pretest and posttest term. Samples that were taken by purposive sampling of 25 people. Data collected includes pre test data first, namely knowledge, data, sodium intake, and potassium. After that post-test data, it is knowledge data about sodium and potassium consumption. Analysis of the data used is the univariate analysis and bivariate analysis.Based on the research from 25 samples given nutritional counseling, the results obtained knowledge about sodium and potassium consumption value of p-value 0,000.In the conclusion of this study is about the influence of nutritional counseling on sodium and potassium consumption that related to hypertension disease.